Antifungal Drugs and Drug-Induced Liver Injury: A Real-World Study Leveraging the FDA Adverse Event Reporting System Database - Zhou, Zhi-Xuan; Yin, Xue-Dong; Zhang, Yu; Shao, Qi-Hui; Mao, Xin-Yu; Hu, Wen-Juan; Shen, Yun-Lin; Zhao, Bin; Li, Zhi-Ling (Frontiers in Pharmacology, 2022)
Aims We aimed to estimate the risk of drug-induced liver injury (DILI) from various antifungal treatments with azoles and echinocandins causing in real-world practice. Methods We performed disproportionality and Bayesian analyses based on data from the first quarter in 2004 to the third quarter in 2021 in the Food and Drug Administration Adverse Event Reporting System to characterize the signal differences of antifungal drugs-related DILI. We also compared the onset time and mortality differences of different antifungal agents. Results A total of 2943 antifungal drugs-related DILI were identified. Affected patients tended to be aged >45 years (51.36%), with more males than females (49.02% vs 38.08%). Antifungal drug-induced liver injury is most commonly reported with voriconazole (32.45%), fluconazole (19.37%), and itraconazole (14.51%). Almost all antifungal drugs were shown to be associated with DILI under disproportionality and Bayesian analyses. The intraclass analysis of correlation between different antifungal agents and DILI showed the following ranking: caspofungin (ROR = 6.12; 95%CI: 5.36-6.98) > anidulafungin (5.15; 3.69-7.18) > itraconazole (5.06; 4.58-5.6) > voriconazole (4.58; 4.29-4.9) > micafungin (4.53; 3.89-5.27) > posaconazole (3.99; 3.47-4.59) > fluconazole (3.19; 2.93-3.47) > ketoconazole (2.28; 1.96-2.64). The onset time of DILI was significantly different among different antifungal drugs (P < 0.0001), and anidulafungin result in the highest mortality rate (50.00%), while ketoconazole has the lowest mortality rate (9.60%). Conclusions Based on the Food and Drug Administration Adverse Event Reporting System database, antifungal drugs are significantly associated with DILI, and itraconazole and voriconazole had the greatest risk of liver injury. Due to indication bias, more clinical studies are needed to confirm the safety of echinocandins.